Foldable slewing crane - Pedrosa, Delfim Duarte Rolo (2008)
This paper describes a slewing crane with electromagnet, operated by three three-phase induction motors but powered from a single-phase power supply. A switchboard drives the motors and the electromagnet. From its seat – mounted on the crane – an operator can make the crane arm slew left or right. The electromagnet can be moved back, forward, up or down and is capable of lifting 80kg loads. Crane slewing is limited to an 180º angle, for safety reasons. Pressing an emergency button switches off all command circuits. An 8051 microcontroller-based system determines the vertical position of the electromagnet, which cannot be switched off while being on a high position, not even if the emergency button is pressed. The crane is made of iron, has a height of 3m and a length of 2,5m. Such proportions make it very suitable for science fair events.